Clinical Cardiology. - Katritsis, Demosthenes G. (OUP Oxford, 2016)
Clinical Cardiology: Current Practice Guidelines provides a detailed summary of the most up-to-date guidelines and trial information as well as the comprehensive authority of a textbook. It is the definitive guide to diagnosis and management in cardiology, allowing readers to quickly obtain reliable information on the best evidence-based care.